The Efficacy of Instagram in Event Marketing: An Empirical Study of Engagement Strategies : Efektivitas Penggunaan Instagram dalam Pemasaran Acara: Analisis Empiris atas Strategi Keterlibatan Audiens - Muhammad Salim, Muhammad Arfin; Asyifa, Melia Sukma (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
This study examines the effectiveness of Instagram as a promotional tool for event organizers in Makassar, specifically focusing on PT. Slemmersindo's strategies. Utilizing qualitative data gathered through interviews with marketing managers, event coordinators, content creators, graphic designers, and customers, as well as observational analysis of the company's Instagram account, the research provides insights into audience engagement and brand visibility. The results reveal that high-quality visual content and consistent branding significantly enhance audience interaction and emotional connection. Additionally, creative and engaging posts not only attract attention but also foster strong relationships with potential customers. The findings suggest that effective use of Instagram allows event organizers to differentiate their brands and provide unique experiences, ultimately improving customer satisfaction and event attendance. Overall, the study highlights the integral role of strategic social media practices in the contemporary event marketing landscape, underscoring the importance of understanding audience preferences and delivering tailored content.